Analysis of the Implementation of Al-Ghazali's Leadership in Improving the Performance of the Leadership of the Faculty of Da'wah and Communication in the Digital Era - Admaja, Dicky Cahya; M. Yati, Abizal (ARZUSIN, 2025)
This study aims to analyze the implementation of the leadership concept of Al-Ghazali in improving the performance of the leadership of the Faculty of Da'wah and Communication in the digital era. The quantitative approach was used with a survey method involving 50 respondents from faculty leaders, lecturers, and education staff at several universities in Indonesia. Data were analyzed using descriptive statistics and linear regression to measure the relationship between Al-Ghazali's leadership principles and improved academic leadership performance. The results of the study show that the leadership principles of Al-Ghazali, which include justice (al-'adalah), wisdom (al-hikmah), exemplary (uswah hasanah), and trust, have been applied significantly in faculty management. The average score of the application of the principle reached 4.25 out of 5, indicating that Islamic leadership values have become an integral part of academic leadership practice. Regression analysis showed a significant positive relationship (R² = 0.72, p < 0.05) between the implementation of Al-Ghazali's leadership and the improvement of leadership performance, especially in the aspects of decision-making, internal communication, and innovation in faculty management. This study concludes that the concept of Al-Ghazali leadership has strong relevance in increasing the effectiveness of academic leadership, especially in facing the challenges of digitalization in Islamic higher education. Therefore, leadership training based on Islamic values needs to be strengthened in order to optimize the quality of faculty management in the digital era.